2012
DOI: 10.1038/mp.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

An environmental analysis of genes associated with schizophrenia: hypoxia and vascular factors as interacting elements in the neurodevelopmental model

Abstract: Investigating and understanding gene-environment interaction (G Â E) in a neurodevelopmentally and biologically plausible manner is a major challenge for schizophrenia research. Hypoxia during neurodevelopment is one of several environmental factors related to the risk of schizophrenia, and links between schizophrenia candidate genes and hypoxia regulation or vascular expression have been proposed. Given the availability of a wealth of complex genetic information on schizophrenia in the literature without know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 129 publications
(147 reference statements)
4
85
0
Order By: Relevance
“…Further, functional annotation clustering of these affected genes revealed a significant enrichment for pathways involved in energy utilization, protein regulation, and synapse formation, processes important in neurodevelopment (Fig. 3A) (19,20). Similar to the extensive gene expression changes we detected in the hypothalamus, we also found robust differences in the brain microRNA environment, where hemizygous placental OGT expression shifted the pattern of 250 of the most abundant brain microRNAs to be distinct from that of wild-type females by hierarchical clustering analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, functional annotation clustering of these affected genes revealed a significant enrichment for pathways involved in energy utilization, protein regulation, and synapse formation, processes important in neurodevelopment (Fig. 3A) (19,20). Similar to the extensive gene expression changes we detected in the hypothalamus, we also found robust differences in the brain microRNA environment, where hemizygous placental OGT expression shifted the pattern of 250 of the most abundant brain microRNAs to be distinct from that of wild-type females by hierarchical clustering analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since we found that rs6265 methylation is related with hOCs which are a risk factor for schizophrenia, 25,35 we assessed the relationship between hOCs exposure, BDNF rs6265 genotype and methylation in PBMCs, and WM performance and related prefrontal activity, 2 well established intermediate phenotypes for this neurodevelopmental disorder. 15 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18 BDNF expression is sensitive to early-life environment [19][20][21] and specifically hypoxic-stressors, 22,23 which, in turn, are critical factors involved in the pathophysiology of schizophrenia. [24][25][26][27] The failure to find association between BDNF and schizophrenia in large-scale case control studies may conceivably reflect a complex interaction of genotype and environmental experience that alters methylation status.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that prenatal maternal immune activation (MIA) (Brown and Derkits, 2010), perinatal hypoxia (Cannon et al, 2002;Schmidt-Kastner et al, 2012), adolescent cannabis use (Arseneault et al, 2004;Henquet et al, 2008), stress (Norman and Malla, 1993), obstetric complications (Dalman et al, 1999), urbanicity (Vassos et al, 2012), migrant status (Cantor-Graae and Selten, 2005), advanced paternal age (Malaspina, 2001), and others (Brown, 2011;Tandon et al, 2008) interact with predisposing genetics to increase risk for illness.…”
Section: Introductionmentioning
confidence: 99%